Determination of Noise Pollution in Local Markets: The Case of Elazığ Province - Gürtürk, Semran Özdem (Fırat University, 2026)
Noise pollution is increasingly recognized as a major environmental problem in contemporary urban areas. Marketplaces, which are established several days a week in densely populated urban districts, represent a particularly relevant case in this context. The elevated voices used by vendors to promote sales significantly increase noise levels, creating adverse psychological and physiological effects on local residents, customers, and vendors working long hours. This study aims to evaluate these impacts with reference to the threshold values defined in the Environmental Noise Control Regulation published in the Official Gazette. The research was conducted in the central district of Elazığ, focusing on the Monday, Tuesday, and Saturday marketplaces. Field observations and in situ noise measurements were complemented by a survey administered to 50 vendors. Noise levels were measured at eight pre-identified points within each marketplace over the course of one week, during morning (09.00–10.00), midday (13.00–14.00), and evening (16.00–17.00) hours. The recorded values were compared with the regulatory threshold levels, and locations exceeding the permissible limits were identified. The findings revealed the specific noise sources that contribute to discomfort among vendors, users, and residents living in the vicinity of the marketplaces. Based on these results, concrete recommendations were proposed for creating more comfortable and sustainable market environments, supported by empirical data.

Günümüzde özellikle kentlerde gürültü kirliliği önemli çevre sorunlarından biridir. Kent yaşamının yoğun olduğu bölgelerde haftanın birkaç gününde farklı yerlerde kurulan, kamusal alanın bir parçası olan pazar alanları bu bağlamda dikkate değer bir örnek teşkil eder. Pazar alanlarında satış amacıyla yükselen sesler gürültü seviyesini artırarak, çevre sakinleri, müşteriler ve uzun çalışma saatlerine sahip pazarcılar üzerinde psikolojik, fizyolojik sağlık açısından olumsuz sonuçlar ortaya çıkarmaktadır. Bu olumsuzlukları önleyebilmek amacıyla resmî gazetede yayımlanan Çevresel Gürültü Kontrol Yönetmeliği kapsamında tanımlanan sınır değerlere göre değerlendirilmesi amaçlanmıştır. Çalışmada Elazığ il merkezinde kurulan Pazartesi, Salı ve Cumartesi pazarları çalışma alanı olarak belirlenmiştir. Yerinde gürültü ölçümü ve saha gözlemlerinin yapıldığı bu çalışmada 50 pazarcı esnafıyla anket çalışması yapılmıştır. Her pazar alanı için gürültü ölçümleri bir hafta boyunca sabah (09.00-10.00), öğle (13.00-14.00) ve akşam (16.00-17.00) saatlerinde her bir pazar alanı için belirlenen 8 farklı noktada ses ölçüm cihazıyla yapılmıştır. Ölçüm yapılan noktalar, araştırma öncesinde sahada yapılan ön incelemeler doğrultusunda belirlenmiştir. Kaydedilen sonuçlar Çevresel Gürültü Kontrol Yönetmeliği’nde verilen sınır değerlerle karşılaştırılarak, bu değerleri aşan noktalar tespit edilmiştir. Yapılan çalışmalar sonucunda, pazar çalışanları, kullanıcılar ve çevre sakinlerinin rahatsızlık duyduğu gürültü etkenleri tespit edilmiş ve gereksinim duydukları konforlu pazar alanının oluşturulması için gerekli koşullar somut verilerle desteklenerek sunulmuştur.
Semt Pazarlarında Gürültü Kirliliğinin Belirlenmesi: Elâzığ İli Örneği
Keywords: Sustainable Architecture; Sürdürülebilir Mimari; Architecture (Other); Mimarlık (Diğer)